Correlation of anomalies of the Pacific surface temperature and the South Oscillation Index - Artamonov, Yu. V.; Babiy, M. V.; Bukatov, O. Ye.; Skripaleva, E. A. (Ukrainian Antarctic Journal, 2009)
On the base of monthly averaged archive data of Pacific SST (array British Atmospheric Data Centre HadISST) and South Oscillation Index (SOI) the cross-correlation functions between SSTanomalies and SOI are calculated for the period 1870-2002. It is shown, that spatial distributions of cross-correlation extremes and its lags are connected with the large-scale features of the surface water structure. The lags of the cross-correlation functions between SST and SOI increases in equatorial zone from east to west, in moderate and polar latitudes, vice versa, from west to east. The speed of propagation of the SST anomalies response on the SOI changes is estimated according to cross-correlation lag.